Structural divergence in binuclear Cu(ii) pyridoxal Schiff base complexes probed by co-ligands: catecholase mimetic activity and sulphide ion sensing. (17th July 2020) - Chakraborty, Moumita; Mondal, Antu; Chattopadhyay, Shyamal Kumar
Abstract : Three Cu(ii ) complexes showing efficient catecholase activity, with pronounced solvent sensitivity, S 2− sensing ability in micromolar concentrations, and coligand dependent denticity of the pyridoxal Schiff base ligand are reported. Abstract : Three hydroxymethyl bridged Cu(ii ) complexes of a pyridoxal Schiff base ligand 4-(( E )-(2-(pyridin-2-yl)ethylimino)methyl)-5-(hydroxymethyl)-2-methylpyridin-3-ol (LH) have been synthesized and characterized on the basis of spectroscopic, elctrochemical and structural properties. The X-ray crystal structures of the complexes reveal dual denticity of the ligand, bidenticity in the absence of a co-ligand as in complex 1, and tridenticity in the presence of a co-ligand such as SCN − /N(CN)2 − as in complexes 2 and 3 . The complexes, though binuclear in the solid state, exist as a monomeric unit in solution due to the exceptionally long axial Cu–Ohydroxymethyl (2.4–2.5 Å) bond. All three complexes show efficient catalytic activities towards the aerial oxidation of 3, 5-ditertiarybutylcatechol (DTBCH2 ) with k cat values of 5.38 × 10 4 h −1, 1.18 × 10 5 h −1 and 1.06 × 10 5 h −1 in methanol. Complexes 1 and 2 also act as a selective sulphide ion sensor with K b values of 6.6 × 10 3 M −1 and 8.1 × 10 3 M −1, respectively, while their respective L.O.D. values are 3.4 μM and 3.2 μM.